PEMIKIRAN KEBANGSAAN K.H. ACHMAD SIDDIQ DAN IMPLIKASINYA DALAM MEMANTAPKAN IDIOLOGI PANCASILA SEBAGAI DASAR NEGARA DI INDONESIA - Ni’am, Syamsun; Nurhayati, Anin (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Agama Islam Negeri Metro, 2018)
Abstract This article addresses an interesting phenomenon of this recent decade in the national journey of Indonesia, where there are some people or certain groups who want to distort or even question Pancasila as the common platform and Indonesian ideology. It is very urgent to examine the thoughts of the charismatic figure of Indonesia, K.H. Achmad Siddiq who has an idea about the relationship among religion, the State, more specifically about the position of Pancasila, and Islam or vice versa, particularly when Indonesia is faced with the movements of the Pancasila de-ideologization which recently comes up to the surface. The most interesting idea of ​​K.H. Acmad Siddiq is